Cost risk assessment for renovating old neighborhood of EPC projects in China using SEM-BNT-MEEM method - Zhang Yinghui; Li Tian (Archives of Civil Engineering)
The transformation of old neighborhood is a significant livelihood project for urban renewal, and promoting the profound transformation of old neighborhood is a significant problem faced by China, while the Engineering Procurement Construction(EPC) model integrates the design, procurement, and construction of the transformation project of old neighborhood, which improves the efficiency and quality of the transformation at the same time, and faces a significant cost risk problem due to the change of fixed lump-sum price contract, so in order to enhance the ability of the general contractor to prevent the cost risk and to improve the transformation project benefits, this study constructs a comprehensive evaluation index system consisting of 19 factors to assess the cost risk in all aspects from environment, technology, management, and economy, which proposes a new type of evaluation method combining structural equation modeling (SEM), blind number theory (BNT), and matter-element extension model (MEEM), and combines with the actual cases of old neighborhood remodeling to arrive at the risk level of the factors and based on the results of the analysis are given to confirm the validity of the model and provides a successful risk assessment tool.